2010
DOI: 10.1007/s11274-010-0372-0
|View full text |Cite
|
Sign up to set email alerts
|

Mobilisation of potassium and phosphorus from iron ore by ectomycorrhizal fungi

Abstract: Mutualistic roles of ectomycorrhizal (ECM) fungi have been linked to their ability to produce organic acids that aid in the dissolution of insoluble minerals in the rhizosphere. This ability of ECM fungi was utilised to investigate their potential participation in the mobilisation of nutrients such as phosphorus (P) and potassium (K) from a typical insoluble ore-iron ore. In vitro pure cultures of four different ECM fungi; Pisolithus tinctorius, Paxillus involutus, Phialocephala fortini, and Suillus tomentosus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 37 publications
1
12
0
Order By: Relevance
“…The solubilization process of minerals may be due to the production of various organic acids such as acetic, formic, gluconic, oxalic and succinic acids Lal (2002). Adeleke et al, (2010) have reported the ability of ectomycorhizal fungi in mobilization of P and K sources from insoluble ore. Greater release of K from muscovite has been recorded in B. muciloginosus (Sugumaran and Janarthanam, 2007) (Table 4).…”
Section: Potassium Releasing Capacitymentioning
confidence: 99%
“…The solubilization process of minerals may be due to the production of various organic acids such as acetic, formic, gluconic, oxalic and succinic acids Lal (2002). Adeleke et al, (2010) have reported the ability of ectomycorhizal fungi in mobilization of P and K sources from insoluble ore. Greater release of K from muscovite has been recorded in B. muciloginosus (Sugumaran and Janarthanam, 2007) (Table 4).…”
Section: Potassium Releasing Capacitymentioning
confidence: 99%
“…and Fe 3? contained in Sishen iron ore (Yuan et al 2004;Delvasto et al 2009;Adeleke et al 2010). Scavenging is one of the methods through which microbes obtain nutrients from minerals, but this condition is mainly created by need.…”
Section: C-o Bond From Carboxylate Ions (Omoike and Chorover 2004) 1314mentioning
confidence: 99%
“…Examples include oxalic, citric, acetic, lactic, tartaric, malic and malonic acids (Wallander and Wickman 1999;Adeleke et al 2010Adeleke et al , 2012. The hyphae of ECM fungi can alter the soil chemistry through the production of OAs, a process that is essential for increased nutrient absorption by plants vis-a-vis plant health (Rasanayagam and Jeffries 1992;Jones et al 2003;Adeleke et al 2012).…”
Section: Introductionmentioning
confidence: 99%